PRINSIP MODERAT DALAM PENJAMINAN MUTU PERGURUAN TINGGI KEAGAMAAN ISLAM SWASTA (PTKIS) (Studi PTKIS di Provinsi Lampung): (Studi PTKIS di Lampung) - Ahmad Fauzan; Pane, Erina; S, Kartika (UHN IGB Sugriwa Denpasar, 2023)
Private Islamic Religious Colleges (PTKIS) are growing and developing. Including in Lampung Province, which has been supported by the existence of Kopertais Region XV Lampung since 2020. The field research described aims to explore a moderate attitude in quality assurance at PTKIS. The objects in this study are representatives of the types of tertiary institutions, namely the Islamic Institute of Religion (IAI), Islamic College of Religion (STAI), College of Tarbiyah Sciences (STIT), Islamic College of Economics and Business (STEBI), Islamic Higher Education College. ah (STIS). The results of the research show that moderation is needed in the implementation of a quality assurance system. This is important because the results of the quality assurance system, both SPMI and SPME will be a benchmark for PTKIS governance which will have an impact on the sustainability of all PTKIS activities. Thus, PTKIS must prioritize a moderate attitude, such as